Heroine - Finley, Erin (InTensions, 2024)
Heroine is a series of images relating a dark love story. It is a rock opera in 2-D, featuring New York City anti-heroes Lou Reed and Nadia Nefariously. The introductory image is a trinity of punk children, soothsayers in a Greek-theatre-style chorus cautioning the lovers of what is to come. The tale’s protagonists both belong to the 1970s underground punk scene, that gladiatorial arena in which affliction and volatility reign. This is translated through the artworks, with Reed portrayed as a dark knight, black subway sludge dripping from his tarnished armour. Nadia Nefariously, best known for her glamorous strip-show performances, is “white light, white heat,” a platinum-haired goddess in rhinestone boots. In a torrent of creative synergy and romantic bliss, the two fuel each other’s most haunting works, Reed’s ambivalent “Heroin” and Nefariously’s “Cinderacula.” Though this “star-cross’d” pair are deeply in love, there is always turbulence and violence between them. The affair becomes a sadomasochistic one, inciting moments of sublime eroticism and ebbs of self-destruction. Ultimately, upon the death-knell entrance of Andy Warhol, Reed and Nefariously are forever separated, their “legendary hearts” demised by a magic realist sea storm. In creating these works I imbue them with the pains of romantic passion-jealousy, fear, sadness-made manifest: mark-making here is raw and explosive, scarring the satin canvas. Reaching heights of 10 and 11 feet, these pieces convey an epic tale through epic proportions. Collage elements and written scraps give the images further dimension and texture. Rendered with various media, from oil paint to Sharpie pen, these images communicate the monstrous and sensual quality of this story in a way that is kinetic and careful, violent and tender. The sheen of the various fabrics suggests trash-glamour and celebrity skin. Contact: erin.finley@sheridaninstitute.ca